Impact of El Niño and El Niño Modoki Events on Indonesian Rainfall - Iskandar, Iskhaq; Lestrai, Deni Okta; Nur, Muhammad (Makara Journal of Science, 2019)
On an interannual time-scale, the Indonesian climate is strongly influenced by the dynamics of Indo-Pacific climate modes. This study aims to investigate the possible impact of different types of El Niño events, namely, typical El Niño and El Niño Modoki, on Indonesian rainfall variability. Seasonal composite analysis was used to evaluate the magnitude and significance level of the influence of El Niño on the rainfall variability over the Indonesian region. Typical El Niño (hereafter El Niño) has a stronger influence on Indonesian rainfall than the El Niño Modoki during boreal autumn in September, October, and November when the events almost reach their peak. Cold sea surface temperature (SST) anomalies were observed in the Indonesian sea and in the western Pacific during El Niño years, while cold SST anomalies covered only the eastern Indonesian sea during El Niño Modoki years. Strong cold SST anomalies during El Niño years led to stronger low-level wind divergence over the Maritime Continent compared with that during El Niño Modoki years. In addition, the Walker circulation during El Niño years revealed a stronger downward motion over the Maritime Continent than that observed during El Niño Modoki years. This stronger downward motion (low-level wind divergence) during El Niño years reduced lower atmospheric water vapor and suppressed atmospheric convection over the Maritime Continent, leading to a significant decrease in rainfall. Similar situations were also observed during El Niño Modoki years but with a much weaker amplitude.